Evaluation of Pending Claims Bakti Timah Karimun Hospital in Assessing the Effectiveness of the V-Claim Application - Yuni Fitriani; Budi Hidayat (International Journal Labs, 2023)
The presence of the VClaim application as a form of innovation in industry-based health services 4.0 seeks to create efficiency in submitting claims by the Hospital. However, in its implementation, especially at the Bakti Timah Karimun Hospital, Pending claims still occur which can disrupt the operation of the Hospital. Based on data obtained by researchers, in January-September 2022 there were pending claims with a total INACBGS of IDR 1,537,233,700, - with 1,353 total cases consisting of 7% inpatient care and 3% outpatient care. This study was conducted to assess the effectiveness of the VClaim application in capturing claims that still require confirmation back to the hospital. In addition to improving claim management as well as being used as material for evaluating V Claim applications in submitting claims for JKN participant patients. This research is a non-experimental observational study with qualitative data collection at the Bakti Timah Karimun Hospital. This research uses document review. The occurrence of Pending Claims at RSBT is caused by certain factors both inpatient and outpatient requiring specific improved data to make it easier for verifiers to verify Hospital claims. The VClaim application algorithm in verifying hospital claims against JKN patients is considered effective in measuring the feasibility of claims submitted by FKRTL or hospitals.